PENGARUH KOMPETENSI PROFESIONAL DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU DIMODERASI BUDAYA SEKOLAH (Studi Kasus Pada Guru SMP Negeri Se-Kecamatan Juwana Kabupaten Pati) - Sunarto, Sunarto; Zulaikah, Zulaikah (Jurnal Ilmiah Telaah Manajemen, 2019)
This study examines the effect of professional competence and emotional intelligence of the teacher's performance organizational moderate culture at junior high school in Juwana districts. This study used primary data. The technic analizesis by using quasi type moderation regression with absolute difference technique. The results showed that Professional Competence, Emotional intelligence and Organizational culture has a positive and significant impact in teacher’s work performance. Organizational culture moderate the influence of the professional competence on the teacher's performance with strengthening functions. But, organizational culture does not moderate the influence of emotional intelligence to teacher’s work performances. Keywords: professional competence, emotional intelligence, performance, organizational culture and moderation.